BALANCING RESOURCES AND VALUE IN DISTANCE EDUCATION COURSE REVIEWS: A CASE STUDY AT A MID-SIZED PUBLIC UNIVERSITY - William Swann; M. Kathleen Cripe (Informascope, 2018)
This study examines the development and implementation of a distance education course review process at a mid-sized public university. Four primary goals were set for the process:  to provide substantive feedback, to cultivate engagement between DE faculty and staff, to provide support to course developers and reviewers, and to establish an effective balance between faculty resources and the value of feedback generated through the process. Feedback was collected through a survey of participating developers and reviewers (n=52). Responses broadly supported achievement of the four primary goals. Those who participated in multiple roles gave stronger ratings on all survey questions than those who participated through a single role. Based on qualitative and quantitative feedback, strengths, weaknesses, and possible adjustments to the process are discussed.